Enhancing Diabetes Patient Education with a Diabetes Education Bundle - Sarah Breitenbach (My University, 2026)
Implementing a structured diabetes patient education bundle. This quality improvement project evaluated the impact of a diabetes patient education bundle on nurse confidence in providing patient education, nurse documentation of patient education, and 30- and 60-day diabetes related readmission rates.
Keywords: diabetes, patient education, nurse confidence